A Business Simulation Course: a Teaching Strategy for Students’ Learning - Pinheiro, Margarida M. (2012)
This article reports on the impact of the implementation of a Business Simulation course in a PBL (problem-based learning) undergraduate Portuguese Accounting programme, designed to enhance graduates’ performance in the labour market. In essence, PBL is an organizational model that promotes the acquisition of knowledge through a staged sequence of contextualized problems of real professional situations that students can integrate in the future. The PBL educational approach is based on pragmatism, practical learning goals and competence, as an individual or team work. Our paper focuses on the power of learning styles, namely the ones inspired by PBL, to influence students’ motivations; and asks to what extent motivation contributes to dissimilar performances. The research was carried out making use of data triangulation (it includes the perspectives of students, graduates and academics), theory triangulation (several streams were used in the literature review) and methodological triangulation (it articulates quantitative and qualitative methodologies). The methodology made use of semi-structured interviews to academics and closed questionnaires to the remaining participants. Based on our evaluation, we argue that it is possible to identify two different types of drivers that may justify the presence and the reinforcement of students’ motivation: extrinsic (related to the real-world features of the model and its pragmatic nature) and intrinsic (related to the innovative aspects of the teaching methods and learning styles). An interesting point, less evident in the literature, is that feedback (mainly from tutors but also from students’ peers) and the possibility of improving the work done, jointly, have a huge importance on the learners’ keenness and motivation. Finally, the idea that stimulating motivation will be reflected in the learning and results of students is of central importance for students’ performance and proactive learning.